A federative model of the Church in western theology - Pavel Ermilov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The author attempts to reconstruct in the most general detail the history of the application of federative terminology to the description of the structure of the Christian Church. The concept of federation appeared in the 18th century in the works of Protestant church historians who believed that the formation of the initial church structure was modeled on the federative political structures that emerged in Greco-Roman antiquity. Further mastering of the relevant political terminology by church authors was facilitated by the formation of the theory of political federalism in the 19th century and its popularization in the political and public life of many states. The author shows how since the end of the 19th century the concept of federation has been applied to the church constitution at its modern stage. This practice was especially characteristic of the representatives of the Anglican Church, in whose official rhetoric the image of federation took an important and prominent place. It was in the midst of the Anglican Church that the formula of the Church as a federation was born. Thanks to Protestant influence, federative terminology enters the language of ecumenical theology, being used there in particular to denote an intermediate form of ecclesiastical union. However, federative formulas in ecclesiology were accompanied by constant criticism, mainly for allegedly bringing with them alien and profane associations. An irreconcilable position was taken by Catholic authors, who for a whole century have been developing a theological refutation of ecclesiastical federalism. Under the influence of their criticism, as well as significant historical and ideological changes, the image of federation gradually disappeared from the language of Christian theology, surviving ultimately in the form of a general and unanimous denial that the Church is not a federation. The author is trying to show that despite some artificiality in the use of federative terminology, there were certain theological insights behind its use concerning the status of particular Churches and the nature of their mutual unity. These intuitions were largely ignored by the general development of ecclesiology in the twentieth century with its main interest in the global and universal dimension of the Church.